The Impacts of Cation Stoichiometry and Substrate Surface Quality on Nucleation, Structure, Defect Formation, and Intermixing in Complex Oxide Heteroepitaxy–LaCrO3 on SrTiO3(001). (23rd January 2013) - Qiao, L.; Zhang, K. H. L.; Bowden, M. E.; Varga, T.; Shutthanandan, V.; Colby, R.; Du, Y.; Kabius, B.; Sushko, P. V.; Biegalski, M. D.; Chambers, S. A.
Abstract The ability to design and fabricate electronic devices with reproducible properties using complex oxides is critically dependent on our ability to controllably synthesize these materials in thin‐film form. Structure‐property relationships are intimately tied to film and interface composition. Here the effect of cation stoichiometry on structural quality and defect formation in LaCrO3 heteroepitaxial films prepared using molecular beam epitaxy is reported. From first principles the regions of stability of various candidate defects, along with the predicted effects of these defects on structural parameters, are calculated as a function of Cr and O chemical potential. Epitaxial LaCrO3 films readily nucleate and remain coherently strained on SrTiO3(001) over a wide range of La‐to‐Cr atom ratios, but La‐rich films are of considerably lower structural quality than stoichiometric and Cr‐rich films. Cation imbalances are accompanied by anti‐site defect formation. Cation mixing occurs at the interface for all La‐to‐Cr ratios investigated and is not quenched by deposition on SrTiO3(001) at ambient temperature. Indiffused La atoms occupy Sr sites. Intermixing is effectively quenched by using molecular beam epitaxy to deposit LaCrO3 at ambient temperature on defect free Si(001). However, analogous pulsed laser deposition on Si is accompanied by cation mixing.